European Capitals of Culture: Residents’ Perceptions - Farmaki, Anna; Christou, Prokopis A.; Saveriades, Alexis (My University, 2018)
This study centres its focus on the esteemed concept of the European Capital of Culture (ECoC), acknowledged as a catalyst for sustainability due to its economic and socio-cultural contribution to host city destinations. Particularly, it examines residents’ perceptions on this foremost cultural event since these are credited with an event’s success. Through a qualitative approach targeting residents of Pafos, a coastal city in Cyprus which served as ECoC in 2017, four categories of residents are identified based on the key dimensions of residents’ perceptions and involvement in tourism. These categories in turn exhibit varying levels of support towards the ECoC, with resident support being primarily shaped by the socio-political context in which cultural events take place as well as residents’ knowledge of the tourism environment. Findings are insightful to tourism stakeholders and contribute to their effort in improving the sustainable management of cultural events.
Keywords: Resident's Perceptions; European Capitals of Culture; Culture; Events